The Impact of Using Cooperative Learning Strategies in Enhancing EFL Learners’ Grammar Achievement - KADDOUR GUETTAOUI, Safia (My University, 2017)
The purpose of this study is to explore the importance of cooperative learning as an effective method for improving the grammar results of EFL secondary school students and its application in grammar teaching; it also aims to know if the grammar of the students will be developed by this strategy. When collecting data, we used quantitative and qualitative research methods. The teacher questionnaire, student questionnaire and classroom observation were used as tools to gather data to achieve our goal. The purpose of the use of questionnaires and observation is to collect data on the attitude of teachers and pupils to the cooperative learning strategy in teaching grammar, to collect data on the level of grammar of the students and on the methodology followed by the teachers, as well as to record information on the supports used by the teachers.
The case of first year scientific students at secondary school
Keywords: Learning grammar; Cooperative learning strategy; EFL secodary teaching